Domestikasi Atas Hegemoni: Peran Pameran Seni "Conversing With Domestic Memories" - Mellynajati Ancas Oryza Tivani; Khairunnisa Sholikhah; Daphne Dinda Mahardika (Ars: Jurnal Seni Rupa dan Desain, 2025)
The research based on the exhibition 'Conversing With Domestic Memories' at Ruang MES 56 from 18th-21st February 2025, explores the concept of domestication, which positions marginalised groups as subordinate elements in the construction of an authoritarian society. This exhibition highlights the less well-known events that have occured in Indonesia, Canada, Chile, Northern Ireland, Nicaragua, Colombia, and Uganda. This research is qualitative study using literature sources. The primary data used in this research are Antonio Gramsci concept of hegemony, Maurice Halbwach's collective memory, Jan Assmann's cultural identity, and Gayatri Chakravorty Spivak's subaltern approach. It aims to review the implementation of the exhibition's role through art as a tool and or a medium in the context of the truth of the dominant version of historical narratives, especially aspects of memory, aspects of power, and aspects of marganalized groups. The researcher employed the data with elements of description, interpretation, intercoherence and critical reflection with a visual analysis component and interviews to examine how an art exhibition relates to the issue of state violence and the provision of a space for the voices of marganalized communities. The result shows that art exhibitions function not only as a medium for revealing historical truths, but also as a tool for fostering solidarity and critical awareness among audiences. A broader perspective reveals the role of art in combating forgetting and impunity, including the role of art in constructing a more inclusive narrative of the past authoritarian society and encompasses the role of the art's as a tool, as a medium, and the synergy between these two functions.